The impact of cortical remapping interventions on pain and disability in chronic low back pain: A systematic review. Issue 1 (March 2015) - Daffada, P.J.; Walsh, N.; McCabe, C.S.; Palmer, S.
Abstract Background Cortical change, in the manner of cortical remapping is a common feature of and potential driver for chronic low back pain (CLBP). Novel interventions such as graded motor imagery (GMI) and mirror visual feedback (MVF) have been shown to facilitate correction of cortical changes and improve symptoms in other chronic pain states. However, little is known regarding the effectiveness of these treatment approaches in CLBP. Objective To identify and assess the current evidence regarding the effectiveness of interventions which target cortical remapping in the management of CLBP. Data sources The electronic databases Medline, Embase, CINAHL, AMED, OVID, PEDro, BNI, PsycINFO, HMIC, and Cochrane library were systematically searched. Study selection Of 11 potential citations identified, 5 articles were identified for inclusion and critiqued. These comprised 3 randomised controlled trials (RCTs), 1 randomised cross-over study, and 1 multiple case study design. Results Visualisation of lumbar movement may significantly improve movement-related pain severity and duration. A combined sensorimotor retraining approach has been shown to produce short-term improvements in both pain and disability outcomes in CLBP. The relative effectiveness of individual interventions and their long-term efficacy have yet to be established. Conclusions There is a paucity of robust literature which has examined the application and efficacy of these novel treatments in the management of CLBP. Results from the few CLBP studies which are available are encouraging. Further, robust research is needed to optimise treatment protocols and establish their long-term effectiveness in CLBP.